Lacerations to Zones VIII and IX: It Is Not Just a Tendon Injury. (24th August 2010) - Fischer, Charla R.; Tang, Peter
Abstract : Extensor tendon injuries are widely believed to be straightforward problems that are relatively simple to manage. However, these injuries can be complex and demand a thorough understanding of anatomy to achieve the best functional outcomes. When lacerations occur in the forearm as in Zones VIII and IX injury, the repair of the extensor tendon and muscle, and posterior interosseous nerve (PIN) is often challenging. A review of the literature shows little guidance and attention for these injuries. We present four patients with injuries to Zones VIII and IX as well as a review of surgical technique, postoperative rehabilitation, and pearls that may be of benefit to those managing these injuries.